Molecular-mass Distribution of Humic Substances from Arctic Soils According to Size Exclusion Chromatography - Lodygin, Evgeny; Vasilevich, Roman (Polish Polar Research, 2020)
Humic substances are polydisperse mixtures of structurally complex matters with different molecular weights. The complexity of molecular composition of humic substances is reflected through their physical and chemical properties and results in diverse interactions both with inorganic components and living organisms. The correlation of the molecular composition of humic and fulvic acids and their molecular weight distribution were analyzed by means of CP/MAS 13C NMR spectroscopy and size exclusion chromatography. Humic acids are a dynamic system containing macromolecular, oligomeric and low-molecular components. Fulvic acids are a monodisperse mixture of relatively low-molecular (up to 2 kDa) organic compounds. A significant correlation between the content of high and medium weight molecular fractions with labile fragments and low molecular weight fractions with hydrophobous fragments of humic acids has been revealed.